The paleoclimatic context for South American Triassic vertebrate evolution. (October 2021) - Mancuso, Adriana Cecilia; Horn, Bruno Ludovico Dihl; Benavente, Cecilia Andrea; Schultz, Cesar Leandro; Irmis, Randall B.
Abstract: The Triassic Period was the setting for the origin and early diversification of Mesozoic ecosystems after the end-Permian mass extinction. The study of the Triassic is essential to understand the evolution of non-marine Mesozoic ecosystems, particularly the vertebrate components and their climatic context. During this time, the configuration of the supercontinent Pangea, which was unique (e.g., the only time since the origin of life that a global supercontinent spread across the equator) in the earth's paleobiogeographic history, is one of the factors that characterized the period. This paleogeographic configuration combined with a high global sea level and no polar ice caps would have had an extraordinary effect on the global climate. Multiple sudden climate events occurred during this time, such as large igneous province (LIP) eruptions, including two that had a major part to play in the major mass extinctions that bracket the Triassic Period. Against this backdrop, a number of modern vertebrate clades originated on land, including lissamphibians, lepidosaurs, turtles, dinosaurs, and mammaliaforms. To test the link between climatic and evolutionary events, we compiled paleoclimatic data from Argentinian, Brazilian, Bolivian, and Chilean Triassic non-marine vertebrate-bearing strata to discuss observed paleoclimatic changes and their influence on vertebrate evolution in South America during this time. Fluctuating climate conditions dominated the western Gondwana Triassic, with arid to semiarid conditions during Early Triassic with marked humid seasonal fluctuation in the continental interior, the seasonal semiarid condition of the Middle Triassic shows more humid seasonality than Early Triassic, and the Late Triassic was dominated by seasonal sub-humid conditions with one or more semi-arid intervals, particularly in the continental interior. Comparisons of the Triassic South American vertebrate fossil record and this paleoclimate record show striking patterns; however, better geochronologic control, paleoclimate proxy records, and sample fossil-bearing strata are necessary to understand these trends. Highlights: Review available geochronologically-constrained paleoclimatic South America data. Compare paleoclimatic data and vertebrate fossil record from the same strata. Fluctuating climate conditions dominated the western Gondwana Triassic. Intriguing patterns are apparent when comparing the Triassic South American vertebrate fossil record to paleoclimate record.